Reservoir characterization for sweet spot detection using color transformation overlay scheme - Ismail, A.; Raza, A.; Gholami, Raoof; Rezaee, Reza (SPRINGER HEIDELBERG, 2020)
Reservoir characterization carried out for the quantitative representation of a reservoir leads to effectively managing the hydrocarbon reservoir. There have been few attempts made to characterize the reservoir and assess the potential of a reservoir for the sweet spots using seismic, geomechanical, and petrophysical characteristics where a combination of seismic and petrophysical characters is often ignored given the complexity of such integration. To the best of our knowledge, none of the studies have provided overall reservoir characterization workflows using the combination of petrophysical and geomechanical attributes for sweet spot detection. This study aims to adopt a new color transformation overlay scheme to assess the potential of reservoirs by identifying the sweet spots that can guide to propose a location for a new well. The core scale measurements and well log interpretation were used to determine the petrophysical and geomechanical properties of a highly complex sandstone reservoir which were used as the input to build a 3D reservoir model. The results obtained indicated that predicting the distribution of sweet spots is an effective scheme for well-planning and field development in the region. Four sweet spots are identified in the studied reservoir based on the color transformation overlay approach which has heterogeneous continuity behavior in vertical and horizontal directions. The identification of sweet spots based on top view is not enough for the complete understanding of spreading in all directions. Cross-sectional analysis of the color transformation overlay model revealed that there is a sweet spot near Well-E in west which has ideal reservoir potential and place to consider another proposed well.